Previous caesarean scar rupture: mortality averted a case report - Kumar, Ajay; Singh, Anuj; Tripathi, V. B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Uterine rupture at the site of a previous cesarean section scar is an uncommon but catastrophic complication of pregnancy by associated with significant foetal and maternal mortality and morbidity. A 31-year old woman, G6P3A2L1 with previous lower segment cesarian section (LSCS), booked case was admitted at 37 week of gestation with complaint of leaking per vaginal (P/V) in our tertiary care centre. Patient had spontaneous labor pain, which subsided after few contractions and sustained hemorrhagic shock with utero placental insufficiency due to previous LSCS scar rupture. Due diligence and expeditious caesarean management strategy needs to be adopted in parturient with previous caesarean patients owing due to risk of scar rupture. Ultrasonography is a useful tool which can be used to assess women with previous cesarean section to carry out risk stratification for subsequent pregnancies.